2020
DOI: 10.5194/egusphere-egu2020-18441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of Southern Africa as a dust precursor to East Antarctica

Abstract: <p>Identifying the provenance of mineral dust depositions in Antarctica is crucial to reconstruct Southern Hemisphere (SH) atmospheric circulation, validate numerical models, evaluate their contribution as micronutrients in the Southern Ocean and assess their control on the climate changes. For the last few decades, it has been demonstrated Southern South America (SSA) is the main precursor of dust reaching Antarctica during both ice ages and interglacial periods (e.g. Gili et al., 2017, 2016). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…On this matter, more recent studies have showed strong support that highlights Southern Africa as a secondary and significant dust supplier to East Antarctica. Sr, Nd and Pb isotope ratios of Antarctic modern dust recovered from snow samples collected along coastal sites of the Dronning-Maud Land area (DML-East Antarctica), have shown similar composition to the Southern Africa sediments 77 . This data is consistent with the results observed using back trajectory FLEXPART particle dispersion transport model where a mix of modern Southern Africa and Southern South America dust sources was clearly spotted in the coastal area of East Antarctica 78 .…”
Section: Discussionmentioning
confidence: 99%
“…On this matter, more recent studies have showed strong support that highlights Southern Africa as a secondary and significant dust supplier to East Antarctica. Sr, Nd and Pb isotope ratios of Antarctic modern dust recovered from snow samples collected along coastal sites of the Dronning-Maud Land area (DML-East Antarctica), have shown similar composition to the Southern Africa sediments 77 . This data is consistent with the results observed using back trajectory FLEXPART particle dispersion transport model where a mix of modern Southern Africa and Southern South America dust sources was clearly spotted in the coastal area of East Antarctica 78 .…”
Section: Discussionmentioning
confidence: 99%